2019
DOI: 10.1002/ijc.32535
|View full text |Cite
|
Sign up to set email alerts
|

Olfactomedin 4 downregulation is associated with tumor initiation, growth and progression in human prostate cancer

Abstract: The olfactomedin 4 (OLFM4) gene has been analyzed as a tumor‐suppressor gene and a putative biomarker in many cancers. In our study, we analyzed the relationship of OLFM4 expression with clinicopathological features and with CpG site methylation in the OLFM4 gene promoter region in human primary prostate adenocarcinoma. OLFM4 protein expression was significantly reduced in prostate cancer tissue compared to adjacent normal tissue and was further significantly reduced in more advanced cancers. Bioinformatic stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…We have previously detected OLFM4 RNA and protein expression in RWPE1 cells 35 . RWPE1 cells are immortalized normal adult prostate epithelial cells whose growth can be maintained under serum-free conditions in 2D culture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously detected OLFM4 RNA and protein expression in RWPE1 cells 35 . RWPE1 cells are immortalized normal adult prostate epithelial cells whose growth can be maintained under serum-free conditions in 2D culture.…”
Section: Resultsmentioning
confidence: 99%
“…The OLFM4 gene plays an important role in innate immunity, inflammation, and cancers 33 . We have reported previously that OLFM4 gene expression was reduced or lost during the progression of prostate cancer due to frequent genetic deletion 34 and hypermethylation of the OLFM4 gene promoter region 35 . The expression of OLFM4 mRNA has been detected in normal prostate tissues, primary-cultured normal prostate epithelial cells, and RWPE1 immortalized normal human prostate epithelial cells 34 36 .…”
Section: Introductionmentioning
confidence: 99%
“…The gliomedin paralog, olfactomedin 4, is a glycoprotein with an olfactomedin-domain, which is involved in numerous intracellular signaling pathways, including NF-κB, and is associated with innate immunity. Furthermore, olfactomedin 4 suppresses the development and progression of cancer [ 50 , 51 ], and tumorigenesis is observed in olfactomedin4 deficient mice [ 52 ]. Thus, it is hypothesized that gliomedin is also involved in the development of bladder cancer by a mechanism similar to that of olfactomedin 4 in innate immunity and oncogenesis in a certain environment.…”
Section: Discussionmentioning
confidence: 99%
“…A post hoc analysis of data from a Phase 3 trial showed that the detection of serum free methylated GSTP1 (mGSTP1) DNA can predict the outcome of chemotherapy in metastatic prostate cancer and may guide treatment decisions in the clinic [26]. In addition, methylation of other genes, including olfactory 4 (OLFM4) [27], MTSS1 [7] and myeloid ecotropic viral insertion site 2 prognosis has yet to be examined in a large prostate cancer dataset. In this study, we tried to explore a classi cation method that integrates several DNA methylation markers to help clinicians evaluate the therapeutic effect and prognosis of prostate cancer patients and choose treatment strategies.…”
Section: Discussionmentioning
confidence: 99%